An Updated Sexual Homicide Crime Scene Rating Scale for Sexual Sadism (SADSEX-SH) - Myers, Wade C. (International journal of offender therapy and comparative criminology, 2019)
The Sexual Homicide Crime Scene Rating Scale for Sexual Sadism (SADSEX-SH) is a rating scale which dimensionally measures the degree of offender sexual sadism in suspected sexual homicide cases. Scoring is accomplished using crime scene and related investigative information. Preliminary norms for the SADSEX-SH prototype indicate that it correctly classified offenders with and without sexual sadism. This study further assessed SADSEX-SH sensitivity, specificity, and inter-rater reliability by comparing a larger sample of male sexual homicide offenders with (n = 20) and without (n = 20) sexual sadism. Two items generally undetectable at crime scenes were removed from the originally proposed 10-item scale, resulting in a final 8-item version. SADSEX-SH total scores for the two groups significantly differed (7.7 ± 3.5, range = 2-14 vs. 2.6 ± 2.0, range = 0-7, t = 5.58, p < .001). Inter-rater reliability was excellent (intraclass correlation coefficients [ICCs] = 0.6-1.0). Using a revised cutoff score of 6, sensitivity was 70.0% and specificity was 90%. This revised scale may prove useful for investigators, clinicians, and institutional professionals in helping to identify and address sexual sadism in sexual homicide offenders.